Internalisasi Nilai Nilai Pendidikan Agama Islam Terhadap Etika Digital Mahasiswa: Studi Korelasional - Muhammad Chusni Fauzan; Ali Murtadho; Didik Wahyudi (Prodi Pendidikan Keagamaan Islam, 2026)
This study aims to determine the relationship between Islamic Religious Education and students’ digital ethics. This research employs a correlational method. The population of the study consists of students from the 2024 cohort of the Islamic Religious Education program at UIN Raden Intan Lampung. The sample includes students from classes C to L of the 2024 cohort in the same program. The sampling technique used is simple random sampling. Data were collected using non-test instruments. Data analysis was conducted using the rank spearman correlation test. The results of the study indicate that there is a positive and significant relationship between Islamic Religious Education and students’ digital ethics. This is evidenced by the rank spearman correlation test, which produced a correlation coefficient of 0.527. This value indicates that the relationship between the two variables falls into the strong category.